International-legal experience in crop insurance in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
The article deals with one of the most important elements of the social functions of the state – the development of insurance in plant growing. The author explores the practice and features of compulsory agricultural insurance in modern Kazakhstan. Agricultural production is known to be exposed to a large number of adverse factors of a different nature. World experience shows that the instrument for solving this problem is the agricultural insurance. Experience of formation of agricultural insurance in Kazakhstan indicates that this type of insurance can not develop without tangible support of the state. Given the importance of the agricultural sector in the national economy and its high dependence on natural and climatic conditions, crop insurance has been classified as a mandatory species. However, compulsory insurance of agricultural land has not led to proper risk management in the agricultural sector.Key words: agriculture, insurance, agriculture, agricultural insurance, agriculture, insurance, agri-food market, agriculture, food products.